Pengaruh Kepemimpinan dan Team Work Terhadap Kinerja Pegawai Pada PT. PLN (PERSERO) Cabang Banda Aceh - Sarboini Sarboini; Jen Surya; Wahyu Safiansyah (Jurnal EMT KITA, 2017)
This research aims to know the influence of leadership and team work against the performance of employees at PT. PLN (Persero) branch of Banda Aceh. This research population totaled 133 employees, and sampling is carried out by technical slovin so retrieved 44 employees as a sample. This model is used in multiple linear regression analysis is. Research results show that leadership and team work have an effect on the performance of employees at PT. PLN (Persero) Branch Banda Aceh, it is proved that the leadership and team work liquid one of the factors that affect the performance of the employees, who evidenced by the results of the research show the percentage of 66.7% 33.3% registration and the rest is influenced by factors other than that there are variables that are examined, such as a work discipline, awards, Wow, there's a cake, compensation and more. The coefficient of correlation (R) value shows that the relationship (correlation) between the free variables with variables of bound 81.7%, the performance of acting employees at PT. PLN (Persero) Branch of Banda Aceh have strong relationships and positive leadership with (X 1) teamwork and (X 2). The f-test statistics testing results demonstrate that leadership and team work simultaneously effect significantly to the performance of employees at PT. PLN (Persero) Branch Banda Aceh, with a value of Fcount > F table (41.083 > 3.226). In partial while leadership and team work effect significantly to the performance of employees at PT. PLN (Persero) Branch Banda Aceh, with a value of tcount > ttable (4, 761dan > 2.017 2.718). Based on multiple linear regression analysis results that both variables are examined, it turns out that variable leadership (X 1), which had the most influence on performance clerk Mottled on PT. PLN (Persero) Branch Banda Aceh with a value koefesien of 0.567 and then occurs followed by the variable work team (X 2) with a value of 0.324.